Upgrading indigenous microfinance institutions in Nigeria: Trials and errors - Hans Dieter Seibel (Universität zu Köln, Arbeitsstelle für Entwicklungsländerforschung (AEF), 2006)
Microfinance is thus not a recent development, and it is not just a temporary solution for poor countries. Every now developed country has its own history of microfinance. It is important to recognize this because it presents a view different from that of many in the microfinance community who associate microfinance with credit NGOs and believe that microfinance was invented in Bangladesh some thirty years ago. Attributing the origin of microfinance to recent initiatives misses not only the historical depth and scale of microfinance, but also centuries of experience, which means: learning from trial and error, failure and success. The beginnings in Europe and Africa, notably in Nigeria, were all informal and small-scale. What distinguishes a country like Germany from many developing countries is not the prevalence of self-help and informal finance at an earlier time. Community- and member-based as well as other informal financial institutions are exceedingly widespread throughout the word. The major difference seems to be the legal recognition given to informal finance in Germany and the protection of the institutions through prudential regulation and effective supervision: an issue which is still controversial in the microfinance community.
Keywords: 330